Avaliação de protocolo para desmame ventilatório em pós-operatório de cirurgia cardiovascular pediátrica - Goraieb, Lilian (2013)
Introduction: Due to the large number of congenital heart disease with several surgical treatment variables involved, it has not yet been established objective protocols for mechanical ventilation weaning in the postoperative period of cardiac surgery. Objectives: To determine the duration of mechanical ventilation (MV) and the success or failure of extubation using an adapted protocol to spontaneous respiratory test in children undergoing cardiac surgery. Patients and methods: A prospective study with 43 operated patients in the Intensive Care Unit under mechanical ventilation for 24 hours or more. They were randomized into two groups: A - Routine (19) and B - Protocol (24). In A, extubation followed routine multidisciplinary team management of intensive care unit. In B, the patients were considered suitable to spontaneous respiratory test after an evaluation. The extubation would occur with the success of the test (120 minutes). The groups were also evaluated according to the severity of the estimated risk. Fisher Bi-Caudal and unpaired student´s t tests were applied. The study was approved by the Research Ethics Committee. Results: There was no statistically significant difference between groups regarding the duration of mechanical ventilatioon (P= 0.81), as well as the success or failure of extubation (P=0.40). Regarding severity, no statistically significant differences were found when evaluated for MV time (P = 0.45 - RACHS 1 and 2) (P=0.59 - RACHS 3 and 4), as well as to success or failure of extubation (P=0.67 - RACHS 1 and 2) ( P= 0.49 - RACHS 3 and 4). Conclusions: The use of the SRT protocol for two hours has not shown to be superior to MV time or to the success or failure of extubation in patients undergoing surgical repair of congenital heart defects.